Are Personality Traits Really Fixed and Does It Matter? - Steven Stillman; Malathi Velamuri (Institute of Labor Economics (IZA), 2020)
A nascent but burgeoning literature examines the importance of non-cognitive skills in determining success across many facets of life. The majority of these papers treat these skills as fixed traits for adults. We estimate the impact of a number of life events on the Big Five personality traits and locus of control. A subset of life events have large impacts on these non-cognitive skills, especially on locus of control. For some events, these impacts persist in the medium-run. We then demonstrate that treating personality traits as fixed can lead to biased estimates of their relationship with socioeconomic outcomes.
Keywords: J24; C18; 330; personality; non-cognitive skills; life events; fixed